Flagellar export apparatus and ATP synthetase: Homology evidenced by synteny predating the Last Universal Common Ancestor. (16th May 2021) - Matzke, Nicholas J.; Lin, Angela; Stone, Micaella; Baker, Matthew A. B.
Abstract: We report evidence further supporting homology between proteins in the F1 FO ‐ATP synthetase and the bacterial flagellar motor (BFM). BFM proteins FliH, FliI, and FliJ have been hypothesized to be homologous to FO ‐b + F1 ‐δ, F1 ‐α/β, and F1 ‐γ, with similar structure and interactions. We conduct a further test by constructing a gene order dataset, examining the order of fliH, fliI, and fliJ genes across the phylogenetic breadth of flagellar and nonflagellar type 3 secretion systems, and comparing this to published surveys of gene order in the F1 FO ‐ATP synthetase, its N‐ATPase relatives, and the bacterial/archaeal V‐ and A‐type ATPases. Strikingly, the fliHIJ gene order was deeply conserved, with the few exceptions appearing derived, and exactly matching the widely conserved F‐ATPase gene order atpFHAG, coding for subunits b‐δ‐α‐γ. The V/A‐type ATPases have a similar conserved gene order. Our results confirm homology between these systems, and suggest a rare case of synteny conserved over billions of years, predating the Last Universal Common Ancestor (LUCA). Abstract : Homologies between proteins of the bacterial flagellum (FliH, FliI, FliJ) and the F1 FO ‐ATP synthetase (FO ‐b + F1 ‐δ, F1 ‐α/β, and F1 ‐γ, respectively) are further supported by shared gene order (synteny), suggesting an ancestral gene cluster that pre‐dates the Last Universal Common Ancestor (LUCA).